Privacy‐preserving smart data storage for financial industry in cloud computing. (23rd August 2017) - Qiu, Meikang; Gai, Keke; Zhao, Hui; Liu, Meiqin
Summary: The recent booming development of cloud computing has enabled a dramatical revolution for current enterprises to create values. Numerous benefits of utilizing cloud services are enhancing the efficiency of improving or creating new businesses. This trend is also associated with the rapid growth of the wireless networks, such as 5G. However, the great increase of deploying clouds also leads to new concerns in data security. One of the major concerns is private leakage that derives from insiders' malicious operations or attacks. This problem has raised a great restriction for financial firms to execute cloud applications. Focusing on this issue, we propose a new solution, entitled Privacy‐Preserving Smart Storage (PS2) model that targets at solving the privacy leakage problems within the existing threat models. The proposed approach uses a novel distributed data storage method to prevent financial enterprises from insiders' massive data mining‐based attacks.